Sensitivity and stability characterization of linear cavity erbium-doped fiber laser for pressure measurement - Mohd Idris S.; Al-Taha M.R.H.; Ismail A.; Abdullah F.; Jamaludin M.Z.; Al-Mansoori M.H. (2023)
This article reports a linear cavity Erbium-doped fiber (EDF) laser for pressure measurement.The fiber laser structure comprises an EDF amplifier, a circulator, an optical coupler, and a fiber Bragg grating (FBG) which is fitted to the shock tube where the pressure is applied. The FBG acts simultaneously as a lasing wavelength selecting component as well as a pressure sensor. The novelty of this sensor lies in its enhanced characteristic with 0.122 nm/bar sensitivity and very good stability with an average power fluctuation of 0.0025 dB over a period of 60 min. Preliminary results have proven to show that the fiber laser sensor is expected to be an attractive choice for long-distance pressure monitoring. 2012 Wiley Periodicals, Inc.